ACCOUNTING SYSTEM RECONSTRUCTION: CASE OF CU SAUAN SIBARRUNG - Pasang, Agustina Rante; Asri, Marselinus; Randa, Fransiskus (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2023)
Purpose – This study aims to reconstruct the credit system by evaluating accounting information systems and conducting in-depth interviews. Design/methodology/approach – Informants were randomly selected from members, managers, and founders of Credit Union Sauan Sibarrung. Findings – Based on the results of interviews with informants from the Manager and Founder of the Sauan Sibarrung Credit Union, information was obtained that the SOP for granting credit at Sauan Sibarrung CU is now standard. It's just that we still must pay close attention to the growth in income and expenses of these members. Associated with the credit termination process Usually, credit termination at the Head Office level, which is authorized by the Deputy, General Manager, CU Sauan Sibarrung Credit Committee or Management, is not processed quickly due to incomplete files from members applying for credit. Originality – Members who became informants in this research case study were all members who had borrowed at the Sauan Sibarrung Credit Union Keywords: Accounting System, Credit Union, Credit System Paper Type Research Result